Pendistribusian Pengelolaan Zakat Infak Sedekah Serta Relevansinya Dalam Meningkatkan Kesejahteraan Yatim Dan Dhuafa Kota Bandar Lampung (Studi Kasus di Lembaga Amil Zakat Nasional Yatim Mandiri Lampung) - Wahyuni, Ridho; Pradikta, Hervin Yoki (Universitas Islam Negeri Raden Intan Lampung, 2021)
The Amil Zakat Yatim Mandiri Institute is an institution that aims to collect and distribute zakat, infaq and alms for the poor and orphans in Lampung Province, especially Bandar Lampung City, in various programs, one of which is the scholarship program. The problem in this article is how is the management and distribution of zakat, infaq and alms at the Yatim Mandiri Lampung national amil zakat institution and its relevance in improving the welfare of orphans and the poor in Bandar Lampung city? The purpose of this study was to analyze the management and distribution of zakat, infaq and alms at the Yatim Mandiri Lampung national amil zakat institution and its relevance in improving the welfare of the orphans and the dhuafa in the city of Bandar Lampung. The research method in this article is seen from the type of field research conducted at the Yatim Mandiri Lampung National Amil Zakat Institute. Primary data was collected through observation, interviews and documentation. The population is all employees of the Amil Zakat Yatim Mandiri Lampung Institute and recipients of ZIS funds. Data analysis used qualitative analysis with a thinking approach using deductive methods. The results of this study, the management of ZIS funds at the Yatim Mandiri Lampung National Amil Zakat Institute (LAZNAS), namely that the collection of zakat infaq and alms funds from muzakki candidates has not been maximized. The total data on the collection and distribution of ZIS funds in the last 3 years from 2018 to 2020 is uncertain (fluctuating) every month. especially in the city of Bandar Lampung. This affects programs and institutional operations, and quotas for receiving benefits for orphans and dhuafa. The more muzakki who give zakat through Yatim Mandiri Lampung, the more the quota of potential beneficiaries (orphans and dhuafa), which aims to increase the welfare of the community, especially the orphans and poor people of Bandar Lampung.Keywords: Distribution of zakat management, Infaq and alms, Yatim Madiri